Construct validity of self-regulated learning in the Covid-19 pandemic era: Exploratory factor analysis - Aviory, Koryna; Saefudin, Abdul Aziz; Gunawan (AIP conference proceedings, 2023)
This study aims to prove the construct validity of student self-regulated learning during the Covid-19 pandemic. Analyzes were performed using exploratory factor analysis to detect and assess latent sources of variation or covariation of the instrument. The research subjects were 108 students. The results of the analysis show that the construct of self-regulated learning during the Covid-19 pandemic consists of five factors, namely self-confidence, self-initiative, discipline and curiosity, learning time management, and self-control. Self-confidence is having self-confidence in doing assignments; do assignments independently; do not give up on solving problems; be confident when facing quizzes/exams; always study hard; take part in online learning activities until the end of the lesson, and dare to express your opinion when discussing. Self-initiative are pay attention to the lecturer’s explanation during the lesson; have a great curiosity in lectures; increase study time to increase grades; keep trying to learn difficult lecture material, and have a target of achieving good college grades. Discipline and curiosity have a learning strategy in lectures; set the learning environment in order to concentrate; take notes on important things when the lecturer explains the material, and asking friends or lecturers when they don’t understand certain material. Learning time management is organizing study time and the spirit of learning in any situation and condition. Self-control is solving and face difficult problems unyielding independently.